Suppression of anti-DNA antibody synthesis in vitro by a cross-reactive antiidiotypic antibody. - Epstein, A (1987)
An understanding of the regulatory mechanisms that govern the humoral immune response will be facilitated by the availability of techniques for the measurement of specific antibody production in vitro. We have developed an enzyme-linked immunosorbent assay system for the measurement of in vitro anti-DNA antibody production by peripheral blood mononuclear cells (PBMC) from patients with systemic lupus erythematosus. Using this technique, the PBMC from 74% of serologically active SLE patients produced levels of anti-DNA antibodies that were greater than 2 SD above the mean of 18 +/- 9 IU/ml for normal subjects. Furthermore, the addition of 3I, a monoclonal anti-idiotypic antibody that recognizes a cross-reactive determinant on anti-DNA antibodies, was shown to specifically inhibit anti-DNA production in vitro.